Prognosis after treatment of villous adenomas of the colon and rectum. - Christiansen, J (1979)
With the existing evidence of neoplastic polyps of the colon and rectum as precursors of most or all colonic cancer, information of the short- and long-term course after treatment is a prerequisite of using the knowledge of the polyp-cancer sequence in an effective cancer prophylaxis. One hundred seventy-four patients treated for villous adenomas of the colon and rectum during the years 1960-1975 were re-examined. Survival and cure rates were estimated by actuarial analysis. The death rate of colonic cancer among patients treated for a benign villous adenoma was significantly higher than in an age and sex matched normal population, resulting in a significantly reduced crude survival rate among these patients. Almost all recurrences after treatment of benign villous adenomas occurred within the first four to five years recurrence rate of roughly 30%, indicating that five years seem to be an adequate total control period following treatment.